Strategy of Developing Oral Vaccine Candidates Against Co-infection of Porcine Diarrhea Viruses Based on a Lactobacillus Delivery System - Guo, Tiantian; Gao, Chong; Hao, Jianhui; Lu, Xiao; Xie, Kun; Wang, Xiaona; Li, Jiaxuan; Zhou, Han; Cui, Wen; Shan, Zhifu; Jiang, Yanping; Qiao, Xinyuan; et al. (Frontiers in Microbiology, 2022)
The number of co-infections with multiple porcine diarrhea viruses has increased in recent years. Inducing mucosal immunity through oral immunization is an effective approach for controlling these pathogens. To generate a multi-pathogen vaccine against viral co-infection, we employed the Lactobacillus vector platform, which was previously used to generate potent candidate vaccines against various diseases. Two strategies were used to test the protective efficiency of recombinant Lactobacillus against multiple diarrhea viruses. First, we used a mixture of recombinant Lactobacillus separately expressing antigens of transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), and porcine rotavirus (PoRV). Next, we used a recombinant Lactobacillus expressing an antigen fusion protein of the above viruses. Twenty-four newborn piglets were divided into three groups and orally immunized with a mixture of recombinant Lactobacillus, recombinant Lactobacillus expressing the antigen fusion protein, or sterile phosphate-buffered saline daily for seven consecutive days after birth. After immunization, the piglets were randomly selected from each group for oral administration of PEDV, and these piglets were then cohabited with piglets without PEDV infection for 7 days. The protective effect against PEDV was evaluated based on clinical symptoms, viral shedding, and intestinal pathological damage. Piglets immunized with recombinant Lactobacillus showed specific mucosal and humoral immune responses to the three viruses and were protected against severe diarrhea and intestinal pathology. Our results highlight the potential of an oral multi-pathogen vaccine based on Lactobacillus to prevent transmission and limit the severity of viral co-infection.